Post-Pandemic Needs of Unpaid Family and Friend Caregivers to Effectively Continue Caregiving Duties in one Northern Ontario Health Authority - Jodi Webber; Erin Mulroney; Mark Tatasciore; Brianna Smith; Patti-Jo Duggan; Louis Ferron; Hannah Albani; Bianca Feitelberg; Laura Tenhagen; Sophia Myles (Patient Experience Journal)
The Covid-19 pandemic had a significant impact on the support networks for older adults and caregivers as health and social care systems were forced to dramatically change the ways patients and clients interacted with providers, services, and programs. In Northern Ontario, caregivers are older, caring in more intense situations, more likely to be caring for multiple care recipients simultaneously and less likely to be in contact with health professionals. This research sought to explore the post-pandemic needs of caregivers in a Northern Ontario health catchment to better understand the needed supports. Using a collaborative and co-design approach with caregiver advisors within a qualitative description design, seven focus groups were conducted with 36 participants in total in February 2023. Reflexive thematic analysis was used to generate five themes from the transcripts: caregivers as the invisible but vital backbone of health and social care; amplified distress: navigating overwhelming demands; family fault lines exposed; contextualized care: the need for personalized supports; and empowering caregivers through training and supports. Our findings suggest that the pandemic significantly impacted the already vulnerable support networks for older adults and caregivers, as health and social care systems had to adapt to new restrictions and limitations. Caregivers were forced to take on additional responsibilities and cope with social isolation, leading to detrimental effects on their mental health and overall well-being.